2015
DOI: 10.3329/bjar.v40i1.23768
|View full text |Cite
|
Sign up to set email alerts
|

Correlation and path coefficients analyses in Basmati rice

Abstract: Correlation and path coefficients analyses among fourteen morphological characters were studied in six advanced lines of Basmati rice and one commercial check namely BRRI Dhan 29. In general, genotypic correlation coefficients were higher than the corresponding phenotypic correlation coefficients suggesting that the environmental influence reduces the relationship between yield and yield contributing characters of rice. Correlation coefficient analysis showed significant positive correlation between plant heig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
15
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 10 publications
26
15
1
2
Order By: Relevance
“…This indicated that simultaneous selection of all these characters was important for yield improvement. Similar kind of association was revealed by Satish Chandra et al, (2009), Nandan andSweta Singh (2010) for days to flowering, Madhavilatha (2002) for days to maturity, Nandan and Sweta Singh (2010) and Ratna et al, (2015) for plant height, Idris and Mohamed (2013) for number of tillers per plant, Eswara reddy et al, (2013), Rahman et al,(2014) for panicle length, Yadav et al, (2010) for number of grains per panicle, Reddy et al, (1997), Madhavilatha et al, (2005) for kernel length and L/B ratio (Table 3).…”
Section: Resultssupporting
confidence: 80%
“…This indicated that simultaneous selection of all these characters was important for yield improvement. Similar kind of association was revealed by Satish Chandra et al, (2009), Nandan andSweta Singh (2010) for days to flowering, Madhavilatha (2002) for days to maturity, Nandan and Sweta Singh (2010) and Ratna et al, (2015) for plant height, Idris and Mohamed (2013) for number of tillers per plant, Eswara reddy et al, (2013), Rahman et al,(2014) for panicle length, Yadav et al, (2010) for number of grains per panicle, Reddy et al, (1997), Madhavilatha et al, (2005) for kernel length and L/B ratio (Table 3).…”
Section: Resultssupporting
confidence: 80%
“…Grain yield per plant was found to be positively and significantly correlated with the traits days to 50% flowering, days to maturity, plant height, number of productive tillers per plant and number of filled grains per panicle at both genotypic and phenotypic levels indicating the relative utility of these traits for selection with respect to grain yield. The positive correlation of grain yield with various traits was supported by Swain and Reddy (2006) for days to 50% flowering, Bornare et al, (2014) for days to maturity, Saikumar et al, (2014) for plant height, Basavaraja et al, (2013) for number of productive tillers per plant and Ratna et al, (2015) for number of filled grains per panicle. The characters panicle length and test weight showed nonsignificant positive correlation with grain yield at both genotypic and phenotypic levels.…”
Section: Resultsmentioning
confidence: 86%
“…Reference [65] also reported that, higher numbers of effective tillers are positively correlated with higher yield. Reference [66] testified that, the number of effective tillers rather than total number of tillers contributes more to enhance productivity of rice plant.…”
Section: Correlation Between Effective Tillers and Filled Grains Alonmentioning
confidence: 98%